Influence of dedicated lanes for connected and automated vehicles on highway traffic flow - Kim, Jongho; Lim, Donghyun; Seo, Younghoon; So, Jaehyun; Kim, Hyungjoo (IET Intelligent Transport Systems, 2023)
The introduction of Connected and automated vehicles (CAVs) promises various social and economic benefits, but safety issues are encountered when CAVs are mixed with human-driven vehicles (HDVs). This study presents three scenarios as lane operation alternatives for situations in which CAVs and HDVs are mixed. The proposed lane operation scenarios for CAVs are the operation of dedicated lanes (DLs) for CAVs, operation of a DL for CAVs and buses, and the operation of DLs for buses. For each scenario, the effects of the market penetration rate (MPR) on traffic efficiency and safety were evaluated. The following findings were obtained from the results: CAVs had a potential effect on each lane according to the lane operation scenario; traffic efficiency and safety improved in a traffic flow situation where CAVs and HDVs were mixed; traffic efficiency and safety were higher when operating DLs for CAVs than when operating a mixed traffic flow; and efficiency and safety were optimal when operating Scenario 2 (DL for CAVs and Buses) in the early stages of introducing CAV (MPR 10–30%) and operating Scenario 1 (DL for CAVs) in the mid- to long-term stages (MPR 40–80%). These findings provide a basis for preparing new policy alternatives to the current policy of adopting DLs for buses. Furthermore, the evaluation of the effects of each DL operation in the transition period where CAVs and HDVs are mixed will contribute to the operation of an efficient and safe CAV-based road traffic system.
Keywords: Automated vehicles; Economic benefits; Highway traffic; Market penetration; Penetration rates; Safety issues; Social benefits; Traffic efficiency; Traffic flow; Traffic safety